Para além das tramas: tecendo sentidos em imagens de tapeçarias artísticas - Secco, Lorilei (2017)
Considering the amount of visual information that comes from all directions, the interest and the need for a greater understanding of such data has boosted this study. The presence of the “image civilization” has become a consensus and, thereby, the Reading and Reader Formation Line of Search of the Postgraduate Program in Letters keeps connected with current thematic axes and promotes investigations that involve artistic languages, which are manifested in diverse supports. Thus, this study brings the tapestry as a representative of textile art and one of the oldest ways of language, which has been condensing stories of people and peoples that are spread all over different regions of the world. However, due to the difficult access to them, the photography is used as a mediator in the image reading, considering them as visual texts subject to interpretation. So, the objective is to investigate the symbols, myths and archetypes that are in the work created as a product of the imaginary of the Brazilian artist Norberto Nicola and the culture in which he was inserted. Methodologically, the research is qualitative, interpretative and bibliographical, and it is completed with the reading of the six visual texts that compose the corpus and it is realized through the Singular Transtextual Image Reading (STIR), which is proposed by Ormezzano (2009a), and which is based on the symbolic hermeneutics of Durand (2002). The theoretical assumptions were based on works of Calabrese (1987), Cáurio (1985), Durand (1989, 1996, 2002, 2004), Gennari (1997), Maffesoli (1995), Martins (1994, 2016), Ormezzano (2001, 2009a, 2009b), Pezzolo (2013), as well as in other authors who have brought essential elements for the development of the research. Therefore, it is expected that the present study may contribute to the strengthening of image reading as an effective reading practice in the academic world, and especially the tapestry to be understood as an artistic language rich in significations.